Effectiveness Of Freestyle Swimming Learning Results Through The Water Fun Games Approach In Primary School Children - Ramadhani, Novi; Wibowo, Ricky; Sumarno, Gano (Jurnal Pendidikan Jasmani (JPJ), 2024)
This research is motivated by the swimming learning process carried out by elementary school students which is still not optimal, such as problems in learning to swim freestyle consisting of fear when learning to swim, and difficulties in carrying out style techniques in body position, leg movements, movement. hands, inhale. The aim of this research is to find out how effective the results of learning to swim freestyle through the water fun games approach are for elementary school children, especially at the Baitul Hikmah Islamic Elementary School. The method used was Quasi Experimental Design in the form of a Pretest-Posttest Control Group, resulting in a calculated sample of 30 children. The instruments used were 3 test instruments, namely psychomotor skills tests, cognitive aspect tests and affective aspect tests. Data was processed using SPSS software through the Paired Sample T Test and grouping the range of criteria values using Norm Reference Assessment (PAN). The results of data processing were carried out using the Paired Sample T-test Hypothesis Test, namely that there was a sig value of 0.000 <0.05, so Ha was accepted. This shows that the results of learning to swim freestyle with psychomotic, cognitive and affective aspects of children improved after being given treatment. Through this research, swimming learning can be made more varied with a variety of fun water games so that children are more enthusiastic about starting to learn freestyle swimming.